A Pragmatic Analysis Of Directive Utterance On The Secret Of Vacul Castle's Comic Strip - Setiawan, Surya, Drs. Sigit Haryanto, M.Hum, Dr. Dwi Haryanti, M.Hum (2015)
This research is a qualitative research. This research proposes to describe the meaning of directive utterance, and to analyze the politeness pattern of each directive utterance found in The Secret of Vacul Castle's comic strip. The data are taken from The Secret of Vacul Castle's comic strip. The methods of collecting data is documentation. The writer collets the data by reading The Secret of Vacul Castle's comic strip, classifying the serial which contains directive utterances, underlining the directive utterances found in The Secret of Vacul Castle's comic, and coding the collected data in the list, in which data list of the data number. The techniques of analyzing data are describing the story context of The Secret of Vacul Castle's comic strip serial, explaining the illocutionary act on the directive utterances found in The Secret of Vacul Castle comic strip serials, determining the category of directive utterances found in The Secret of Vacul Castle comic strip serials, analyzing the politeness strategy used on the directive utterances found in The Secret of Vacul Castle comic strip serials and making the conclusion as the result of the research. The results of the research are: 1) The meaning of directive utterance are 6 data or 20 % as the commanding category, 14 data or 46.67 % as the requesting category, 7 data or 23.33 % as the warning category and 3 data or 10% as the suggesting category, 3)The politeness strategies found of directive utterance in The Secret of Vacul Castle's comic are 12 data or 40 % as the bald on record strategy, 1 data or 3.33 % as the off-record strategy, 10 data or 33.33% as the positive politeness strategy and 7 data or 23.33% as the negative politeness strategy.